Using Active Mediators and Passive Extractors Inside Materialized Data Integration Systems - Cardoso, Paulo V. M.; Franzin, Flavio F.; Mergen, Sergio L. S. (Anais do Concurso de Trabalhos de Iniciação Científica da SBC (CTIC-SBC); 2016: Anais do XXXV Concurso de Trabalhos de Iniciação Científica da SBC, 2016)
Materialized data  integration  architectures are generally composed by active extractors and passive mediators, where the extractors have the goal of forwarding to the mediator all identified objects that may be of interest. This one hand communication road may lead to the difficulty of identifying relevant objects (specially if the source is not well structured) and a waste of energy analyzing irrelevant objects and possibly extracting them. Also, there is a processing overhead associated with the deduplication of objects that are already mapped. In this paper we propose an extension of the integration architecture that allows mediators to play a more active role, guiding passive extractors as to what objects need to be extracted and how they can be identified. We present a case study that shows how passive and active extractors can coexist under the same data integration system.